STMS markers related to Ascochyta blight resistance in chickpea - ÖZYİĞİT, İBRAHİM İLKER; GENÇ, MUSTAFA (My University, 2023)
Chickpea (Cicer arietinum L.) is one of the important legume crops and is cultivated large-scale throughout Turkiye as well as the world. Ascochyta blight, caused by the fungal phytopathogen Ascochyta rabiei, is the leading reason for the highest yield losses among the diseases known for chickpea. The pathogen exhibits high genetic diversity in Turkiye. Therefore, resistancy using Sequence Tagged Microsatellite Site (STMS) markers related with the genes that provide resistance against Ascochyta blight was investigated for the 205 chickpea breeding lines grown in different parts of Turkiye. The analysis for Ascochyta blight resistance was performed using Ta2, Ta146 and Ts54. It was demonstrated that Ta2, Ts54 and Ta146 were the STMS markers having distinguishable features for the detection of Ascochyta blight resistance and were shown to be used in credible fashion for the selection of resistant chickpea breeding lines.
Keywords: Tıp; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyofizik; Biyokimya; Temel Bilimler; Medicine; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Fundamental Medical Sciences; Biophysics; Biochemistry; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Yaşam Bilimleri (LIFE); BİYOFİZİK; Biyoloji ve Biyokimya; BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); BIOPHYSICS; BIOLOGY & BIOCHEMISTRY; İlaç Keşfi; Biyokimya (tıbbi); Yapısal Biyoloji; Moleküler Biyoloji; Klinik Biyokimya; Kanser Araştırmaları; Yaşlanma; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Genel Biyokimya, Genetik ve Moleküler Biyoloji; Drug Discovery; Biochemistry (medical); Structural Biology; Molecular Biology; Clinical Biochemistry; Cancer Research; Aging; Biochemistry, Genetics and Molecular Biology (miscellaneous); General Biochemistry, Genetics and Molecular Biology; Ascochyta rabiei; Cicer arietinum; Didymella rabiei; Molecular breeding; Molecular markers; Yield losses; CICER-ARIETINUM L.; POPULATION-STRUCTURE; IDENTIFICATION; VALIDATION; RABIEI; QTLS